1981
DOI: 10.1136/adc.56.7.517
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-responsive nephrotic syndrome and allergy: immunological studies.

Abstract: SUMMARY Immunological studies were performed on 84 children with steroid-sensitive nephrotic syndrome as part of an investigation of the relationship between steroid-responsive nephrotic syndrome and allergy. Serum total IgE levels tended to be raised, particularly in children who had frequent relapses of nephrotic syndrome. Ten children had extremely high levels (> 1500 IU/ml) and several of them had neither a history of atopy nor any other identifiable cause. 25% of the children had at least one positive tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
(3 reference statements)
4
50
0
2
Order By: Relevance
“…The patient did not suffer from any disease, such as liver dysfunction or parasitosis, which would elevate the IgM. High IgM levels have been reported among children suffering from the nephrotic syndrome, another disease of unknown aetiology with associated atopic manifestations (Meadow et al 1981, Giangiancomo et al 1975 In view of the excellent clinical result in this case, we suggest that other cases of JRA which are seronegative, lactase-deficient and have a family history of milk allergy, be given a 3-week trial of a diet completely free of cow's milk protein.…”
Section: Discussionmentioning
confidence: 97%
“…The patient did not suffer from any disease, such as liver dysfunction or parasitosis, which would elevate the IgM. High IgM levels have been reported among children suffering from the nephrotic syndrome, another disease of unknown aetiology with associated atopic manifestations (Meadow et al 1981, Giangiancomo et al 1975 In view of the excellent clinical result in this case, we suggest that other cases of JRA which are seronegative, lactase-deficient and have a family history of milk allergy, be given a 3-week trial of a diet completely free of cow's milk protein.…”
Section: Discussionmentioning
confidence: 97%
“…1,3 Thirty percent of the patients with steroid-sensitive nephrotic syndrome (SSNS) have been shown to have allergic symptoms (e.g., asthma, allergic rhinitis, atopic dermatitis and urticaria). [1][2][3][4] Nephrotic syndrome may be activated by inhaled allergens (pollens, dust and mold), food allergens or allergic reactions. Fanconi et al 5 were the first in 1951 to show that children with nephrotic syndrome exhibited hypersensitivity in the skin test.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have associated INS with allergy risk of clinical and immunological features (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the 1950s through the 1970s, few anecdotal reports described patients who developed INS after allergic reactions to inhaled allergens, vaccinations, food, or insect stings (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Children with INS commonly have elevated serum levels of immunoglobulin E (IgE), which also plays a central role in allergic inflammation (11)(12)(13)(14)(15)(16). Although clinical and immunological studies have shown a possible link between allergic diseases and INS for 50 y, human epidemiologic study using a large cohort to investigate the relationship between these disorders are lacking (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Asthma is one of the most common allergic disease in childhood, affects a multitude of patients worldwide (22).…”
mentioning
confidence: 99%